(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
For the first time, comprehensive studies were conducted on four high-mountain lakes of Armenia to study their bathymetry, bottom sediment composition, geomorphological structure of basins and the spread of nivation and solifluction processes associated with altitudinal zonation and the presence of seasonal permafrost. It is noted that solifluction is better manifested on the slopes of slag cones (loose friable soil), and the displacement of chingils on steep slopes of volcanic lava flows.